2015
DOI: 10.1002/cbin.10540
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of DNA methyltransferases and genomic imprinting in cloned goat fibroblasts

Abstract: Somatic cell nuclear transfer (SCNT) is a useful way to produce cloned animals. However, SCNT animals exhibit DNA methylation and genomic imprinting abnormalities. These abnormalities may be due to the faulty epigenetic reprogramming of donor cells. To investigate the consequence of SCNT on the genomic imprinting and global methylation in the donor cells, growth patterns and apoptosis of cloned goat fibroblast cells (CGFCs) at passage 7 were determined. Growth patterns in CGFCs were similar to the controls; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Generally, imprinting disorder results in the developmental abnormalities of cloned animals and low cloning efficiency [ 4 ]. Here, we demonstrated that the imprinting status in PFFs derived from the morphologically abnormal cloned fetuses was disrupted, coinciding with the previous report [ 20 ]. Notably, along with the smaller sizes of the abnormal cloned fetuses, the even lower methylation levels and more disrupted expression patterns of imprinting genes were observed.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, imprinting disorder results in the developmental abnormalities of cloned animals and low cloning efficiency [ 4 ]. Here, we demonstrated that the imprinting status in PFFs derived from the morphologically abnormal cloned fetuses was disrupted, coinciding with the previous report [ 20 ]. Notably, along with the smaller sizes of the abnormal cloned fetuses, the even lower methylation levels and more disrupted expression patterns of imprinting genes were observed.…”
Section: Discussionsupporting
confidence: 92%
“…In the previous study, PDX1 ‐modified pigs have been generated by SCNT, which strategy is commonly used to generate mutant pigs (Kang et al, 2017). Although SCNT enables to generate mutant pigs carrying desired mutations, the use of this technique is associated with small litter sizes, low viability, and abnormal epigenetic regulation of resulting offsprings (Kurome et al, 2013; Wan et al, 2016; Zhao, Whyte, & Prather, 2010). In this study, we used electroporation mediated gene editing to establish viable founder generations rescued by mosaicism and carrying PDX1 mutations in their germline to provide monoallelic/biallelic F1 generations.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative Real-Time PCR (qRT-PCR) was implemented using a previous researched method [ 24 ]. The relative mRNA expression levels of target genes were calculated using the comparative 2 −ΔΔCt method after normalization to GAPDH control.…”
Section: Methodsmentioning
confidence: 99%